Sinergi BUMDes dan Home Industry dalam Pengolahan Singkong Gajah menjadi Tepung Mocaf: Solusi Inovatif untuk Kemandirian Ekonomi Desa Sungai Bawang - Adnan Putra Pratama; Ahmad Zamroni; Andi Lisnawati (Jurnal Surya Masyarakat, 2025)
Sungai Bawang Village is one of the villages with promising potential in the agricultural sector, particularly for giant cassava commodities. At the same time, the Sungai Bawang Village-Owned Enterprise (BUMDes) has not yet established an agricultural product processing unit. Therefore, the concept of combining BUMDes with home industry development emerges as a model to enhance the local economy by processing giant cassava into modified cassava flour (MOCAF). MOCAF is a value-added product derived from cassava through a fermentation process, offering health benefits as well as high economic value. The methods employed in this community empowerment partnership program include observation and planning, socialization, training, technology implementation, and ongoing mentoring and evaluation. The outcomes of the program include improved community capacity in processing cassava into MOCAF, the adoption of appropriate technology, and increased knowledge of the procedures for obtaining food product legality certifications. Prior to the program, the community had little awareness of the potential of cassava as a raw material for MOCAF production. Now, they possess a better understanding of the production process, the health benefits, and the economic opportunities for development through BUMDes–home industry collaboration. This program is expected to further enhance community knowledge in agricultural product processing. BUMDes can take an active role, in accordance with its function, as an instrument for strengthening the village economy by developing a community-based home industry model as one of its business units to stimulate economic activities within the village.